DETERMINANT FACTORS ASSOCIATED WITH PATIENT SAFETY CULTURE IN DHARMA YADNYA GENERAL HOSPITAL, BALI - Ede Surya Darmawan; Putu Darmika (Faculty of Public Health, Sriwijaya University, 2019)
Patient safety is a global issue where the achievement is low, so that it needs to implement a patient safety culture. The patient safety culture is measured based on 12 elements of the patient's safety culture according to AHRQ and the application of 6 patient safety goals. Perceived causes of the problem is the work environment, team work, leadership, job satisfaction and job stress. At RSU Dharma Yadnya Denpasar, the staff's perception about patient safety culture is not known yet, but the incident rate is still high. The purpose of this research is to know the relation of determinant of factor which is related to patient safety culture. This research method is quantitative research with cross sectional design which analyzed by PLS, with sample of nurses and midwife implementer which is 72 respondent. The results of this study indicate that there is a significant correlation between work team, leadership, and work stress with the patient safety culture, respectively 3.707, 12.647, and 3.135> T Statistics 1.96. While there is no significant relation between work environment and job satisfaction with patient safety culture equal to 1,336 and 0,328 <T Statistic 1,96. This study concludes that teamwork, decreased levels of work stress and the application of transformational leadership models need to be applied in an effort to improve the patient safety culture in the hospital. Keywords: Determinants factors, patient safety culture